Association Between External Cephalic Version and Body Mass Index For Nonvertex Presentation [A266]. (May 2022) - Prewitt, Kristin; Hersh, Alyssa R.; Fennimore, Nicole; Bullard, Kimberley; Boniface, Emily; Valent, Amy
Abstract : INTRODUCTION: External cephalic versions (ECVs) are critical to preventing the primary cesarean section. We sought to assess the association between indication for ECV and pre-pregnancy BMI. We defined indicated for ECV by those who either had a non-cephalic presentation at delivery or had undergone ECV during pregnancy. METHODS: We conducted a retrospective cohort study using 2014–2018 National Vital Statistics Birth Data. Inclusion criteria were singleton, non-anomalous, >36 weeks gestation deliveries without prior cesarean. Those with missing data for BMI, delivery presentation, or ECV performed were excluded. We assessed rates of ECVs performed based on pre-pregnancy BMI categories (underweight, normal, overweight, and obese). Chi-square and multivariable logistic regression were performed for statistical analyses. We adjusted for age, race, ethnicity, and parity as confounders. All analyses were conducted using STATA version 17. RESULTS: Of the 549, 422 patients included, 8.0% underwent an ECV. When assessed by BMI category, 7.6% in the underweight category, 8.6% in the normal category, 7.9% in the overweight category, and 7.2% in the obese category underwent indicated ECV. After adjusting for confounders, compared to normal weight patients, the odds of undergoing indicated ECV were 0.89 (0.84–0.94) for underweight patients, 0.91 (0.89–0.93) for overweight patients, and 0.81 (0.79–0.83) for obese patients. CONCLUSION: We found that the majority of patients eligible for ECV did not undergo ECV. The rates of attempted ECV are lower for patients with abnormal BMI. Future studies should assess the differences in rates of ECV by BMI and harms of primary cesarean section in these patients.